Drought assessment in Büyük Menderes Basin of Turkey - Mersin, Denizhan; Safari, Mir Jafar Sadegh; Vaheddoost, Babak; Tayfur, Gökmen (My University, 2021)
Drought is one of the most important phenomenon related to the agriculture-food and socio-economic problems all over the world. The Aegean region has a variety of water resources, including but not limited to seacoasts, lakes, streams, and groundwater aquifers. For this reason, the evaluation of historical and future drought events and their effects on water resources is important in the planning and development of the region. In this context, this study aims to evaluate the historical droughts in the inner Aegean region. Monthly precipitation time series were used in three meteorology stations, which are in the Büyük Menderes basin and have a continental climate, recorded between 1973 and 2020. First, to figure out whether the drought analysis is correct and dependable, consistency, randomness, and trend in time series were investigated using the binary mass curve, run and linear trend tests. Next, the standardized precipitation index SPI is used in conjunction with the moving average (MA) operator to evaluate the historical gap associated with meteorological (SPI-1), agricultural (SPI-3), and hydrological (SPI-6 and SPI-12). Finally, the results are evaluated based on the behavior of the SPI time series at different time intervals.
Bildiri - Yayımlanmış
Bildiri - Kongre ve Sempozyum
Keywords: Kuraklık; Hidroloji; İnşaat mühendisliği